Real-world data of dacomitinib as first-line treatment for patients with EGFR-mutant non-small-cell lung cancer - Ji Eun Shin; Hyun Ae Jung; Sehhoon Park; Jong-Mu Sun; Se-Hoon Lee; Jin Seok Ahn; Myung-Ju Ahn; Byoung Yong Shim (Scientific Reports)
Abstract Dacomitinib demonstrated superior survival benefit compared to gefitinib as a first-line treatment in non-small cell lung cancer (NSCLC) patients with common EGFR mutations through ARCHER 1050. However, there is limited real-world data concerning its efficacy and safety. This study included patients with EGFR-mutant NSCLC who received dacomitinib as a first-line treatment between January 2021 and December 2022 at Samsung Medical Center and St. Vincent’s Hospital. This study assessed the objective response rate (ORR), progression-free survival (PFS), overall survival (OS), safety profile of dacomitinib, and subsequent treatments after dacomitinib failure. In total, 153 patients were included in this study. Exon 19 deletion was observed in 50.3% of patients, while the L858R mutation in exon 21 was observed in 46.4% of patients. 45.1% of patients had brain metastasis. The ORR was 84.3%. The median follow-up duration was 16.9 months, with a median PFS of 16.7 months (95% CI, 14.4 to 25.2). Based on the type of EGFR mutation, the median PFS was 18.1 months (95% CI, 14.5 to NE) in patients with exon 19 deletion, and 15.9 months (95% CI, 12.5 to NE) in patients with L858R mutation. Grade 3 or higher adverse events were observed in 7.2% of patients. Initially administered at a dose of 45 mg, dose reduction was necessary for 85.6% of patients, with a final dosage of 30 mg in 49.0% and 15 mg in 36.6% of cases. Out of the 60 patients who experienced disease progression, 31 underwent tissue re-biopsy and 25 underwent liquid biopsy. Overall, T790M mutation was detected in 40.9% of patients who progressed after dacomitinib. The survival benefit of dacomitinib has been demonstrated, indicating its promising efficacy in a real-world setting. The detection rate of the T790M mutation after dacomitinib treatment failure was comparable to that of other second-generation EGFR-TKIs.